Heart Rate and Muscle Oxygenation Kinetics During Dynamic Constant Load Intermittent Breath-Holds - Janne Bouten; Sander De Bock; Gil Bourgois; Sarah de Jager; Jasmien Dumortier; Jan Boone; Jan Boone; Jan G. Bourgois; Jan G. Bourgois (Frontiers in Physiology, 2021)
Introduction: Acute apnea evokes bradycardia and peripheral vasoconstriction in order to conserve oxygen, which is more pronounced with face immersion. This response is contrary to the tachycardia and increased blood flow to muscle tissue related to the higher oxygen consumption during exercise. The aim of this study was to investigate cardiovascular and metabolic responses of dynamic dry apnea (DRA) and face immersed apnea (FIA).Methods: Ten female volunteers (17.1 ± 0.6 years old) naive to breath-hold-related sports, performed a series of seven dynamic 30 s breath-holds while cycling at 25% of their peak power output. This was performed in two separate conditions in a randomized order: FIA (15°C) and DRA. Heart rate and muscle tissue oxygenation through near-infrared spectroscopy were continuously measured to determine oxygenated (m[O2Hb]) and deoxygenated hemoglobin concentration (m[HHb]) and tissue oxygenation index (mTOI). Capillary blood lactate was measured 1 min after the first, third, fifth, and seventh breath-hold.Results: Average duration of the seven breath-holds did not differ between conditions (25.3 s ± 1.4 s, p = 0.231). The apnea-induced bradycardia was stronger with FIA (from 134 ± 4 to 85 ± 3 bpm) than DRA (from 134 ± 4 to 100 ± 5 bpm, p < 0.001). mTOI decreased significantly from 69.9 ± 0.9% to 63.0 ± 1.3% (p < 0.001) which is reflected in a steady decrease in m[O2Hb] (p < 0.001) and concomitant increase in m[HHb] (p = 0.001). However, this was similar in both conditions (0.121 < p < 0.542). Lactate was lower after the first apnea with FIA compared to DRA (p = 0.038), while no differences were observed in the other breath-holds.Conclusion: Our data show strong decreases in heart rate and muscle tissue oxygenation during dynamic apneas. A stronger bradycardia was observed in FIA, while muscle oxygenation was not different, suggesting that FIA did not influence muscle oxygenation. An order of mechanisms was observed in which, after an initial tachycardia, heart rate starts to decrease after muscle tissue deoxygenation occurs, suggesting a role of peripheral vasoconstriction in the apnea-induced bradycardia. The apnea-induced increase in lactate was lower in FIA during the first apnea, probably caused by the stronger bradycardia.